On the Liber de wazalkora, A 12th-Century Treatise on the Astrolabe - Nothaft, C. Philipp E. (Aestimatio, 2023)
“Liber de wazalkora” is the title of an unpublished Latin treatise on the construction and use of the planispheric astrolabe, which appears to have been compiled in southeast Germany (Bavaria) in the second half of the 12th century. It is to a large extent derived from other astrolabe sources available in the Latin West before 1100, but also contains material that has no precedent in any of the known literature. The analysis presented in this article concentrates on the Liber de wazalkora’s section on the use of the astrolabe, which is unusual for both its extraordinary length and frequently atypical astronomical content. A study of the Arabic loan vocabulary in this section leads to the conclusion that some parts of the text were derived from an unidentified Arabic source, presumably via a Latin intermediary.